A Case of Dynamic Molecular Profile in Metastatic Lung Adenocarcinoma and the Significance of Multiple-site Testing - Paturu, Radha; Lingaiah, Raghavendra; Singh, Shalini; Kumari, Niraj; Krishnani, Narendra (Asian Pacific Journal of Cancer Biology, 2024)
Lung adenocarcinomas show intratumoral heterogeneity which has significant impact on the selection of targeted therapy. Multiple molecular sub-clones coexist within an individual tumour which determine recurrence and metastasis formation which is often under-evaluated in a single-site needle biopsy. Our case report demonstrates this intriguing phenomenon and the importance of multiple-site molecular testing to determine the dominant molecular alteration, and initiating the appropriate targeted therapy for better prognosis. Molecular testing from accessible metastatic sites in lung cancer is recommended for a complete assessment of prognosis and therapeutic options in recurrent and metastatic disease.